2018
DOI: 10.1007/s12070-018-1259-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Eustachian Dysfunction and Primary Sclerotic Mastoid Pneumatisation Pattern in Aetiology of Squamous Chronic Otitis Media: A Correlative Study

Abstract: Squamous chronic otitis media (COM) implies formation of a retraction pocket (inactive form) or frank cholesteatoma (active form) in pars tensa or pars flaccida of tympanic membrane. A retraction pocket or frank cholesteatoma are believed to occur due to tubal dysfunction. The present study was undertaken to investigate the pattern of mastoid pneumatisation and Eustachian dysfunction by dynamic slow motion videoendoscopy (DSVE) in cases of both, active and inactive type of squamous chronic otitis media (COM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Post-operative middle ear retraction occurs in tympanoplasty with mastoidectomy much more than tympanoplasty without mastoidectomy. Some of the related studies were reviewed [12,13]. Jain et al reported on role of eustachian dysfunction and primary sclerotic mastoid pneumatisation pattern in aetiology of squamous chronic otitis media [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative middle ear retraction occurs in tympanoplasty with mastoidectomy much more than tympanoplasty without mastoidectomy. Some of the related studies were reviewed [12,13]. Jain et al reported on role of eustachian dysfunction and primary sclerotic mastoid pneumatisation pattern in aetiology of squamous chronic otitis media [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the related studies were reviewed [12,13]. Jain et al reported on role of eustachian dysfunction and primary sclerotic mastoid pneumatisation pattern in aetiology of squamous chronic otitis media [12]. Methwani and Deshmukh reported about Type I Tympanoplasty with or without mastoidectomy in tubotympanic type of chronic suppurative otitis media patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…15 The importance of the ET in the middle ear has been demonstrated in many studies. 14,16 The distal cartilaginous section of the ET has been primarily held responsible for obstructive ET dysfunction. 17,18 In contrast, there are also studies claiming that the area where most obstruction occurs is the bony section of the ET.…”
Section: Discussionmentioning
confidence: 99%
“…KS is more persistent in adults than in children in the temporal bone. In a few investigations, KS was observed in chronic otitis media with squamosal disease [ 21 ]. Middle ear ventilation being obstructed by the anatomical blockage is another reason that may contribute to the development of COM.…”
Section: Reviewmentioning
confidence: 99%